PENGARUH PERAN PEMBIAYAAN MUDHARABAH TERHADAP PERKEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) DI BNI SYARIAH CABANG MEDAN - Nailul Maulidatul Barakah (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2021)
Mudharabah financing is one of the products that is in great demand by the public, especially MSME actors, this is because through mudharabah financing it can develop the business results of MSMEs in the community, but in this study the authors saw that mudharabah financing during the last five years had decreased. It is interesting for the author to see the relevance of the influence of mudharabah financing on the development of Micro, Small and Medium Enterprises. Based on the problems above, the researcher wants to know more about "The Influence of the Role of Mudharabah Financing on the Empowerment of Micro, Small and Medium Enterprises at BNI Syariah Medan Branch, West Medan District, Medan City. Based on the background of the problem described above, it can be formulated the research question is whether there is an influence of the Role of Mudharabah Financing on Micro, Small and Medium Enterprises at BNI Syariah in 2016 – 2019. The research approach used is a quantitative research method. With a sample of 97 people. Based on the research, it can be concluded that there is an influence of the Role of Mudharabah Financing on the Empowerment of Micro, Small and Medium Enterprises at BNI Syariah Medan Branch, West Medan District, Medan City, this can be seen from the results of t-count greater than t-table or t-count 2.756 t-table 1980. Based on the determinant test, it shows that the development of MSMEs is influenced by the mudharabah financing variable by 60.4%, the rest is influenced by other factors.